COMPOSITION OF RIBONUCLEIC ACID FROM VARIOUS PARTS OF SPIDER OOCYTES - Edström, Jan-Erik (The Rockefeller University Press, 1960)
Microphoretic purine-pyrimidine analyses of the ribonucleic acid (RNA) in nucleoli, nucleoplasm, cytoplasm, and yolk nuclei of spider oocytes have been carried out. The material necessary for the analyses was isolated by micromanipulation. Determinations of the amounts of RNA in the different parts of the cell were also performed. No differences between the composition of RNA in the nucleolus and the cytoplasm could be disclosed. Nucleoplasmic RNA was, on the other hand, distinctly different from that in the nucleolus and in the cytoplasm. The difference lies in the content of adenine, which is highest in nucleoplasmic RNA. The few analyses carried out on yolk nuclei showed their RNA to be variable in composition with a tendency to high purine values. The cytoplasm contains about 99 per cent of the total RNA in these cells, the nucleoplasm about 1 per cent, and the nucleolus not more than 0.3 per cent, although the highest concentrations are found in these latter structures. When considered in the light of other recent findings the results are compatible with the view that nucleolar RNA is the precursor of cytoplasmic RNA.